2008
DOI: 10.1002/ijc.23796
|View full text |Cite
|
Sign up to set email alerts
|

CCAAT/enhancer binding protein‐alpha polymorphisms occur more frequently than mutations in acute myeloid leukemia and exist across all cytogenetic risk groups and leukemia subtypes

Abstract: CCAAT/enhancer binding protein-alpha (CEBPA) belongs to a family of leucine zipper transcription factors necessary for late differentiation events of many cell types. CEBPA gene has recently been recognized as the target of genetic alterations in acute myeloid leukemia (AML). CEBPA mutations and polymorphisms were determined in a large series of Southeast Asian AML (n = 247) using polymerase chain reaction and direct sequencing. Chromosome and FLT3 mutation analyses were also undertaken. Thirtytwo distinct typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
(70 reference statements)
1
8
1
2
Order By: Relevance
“…Seventeen novel mutations were reported in the present study, remaining nine mutations were already reported in previous studies (Pabst et al, 2001;Leecharendkeat et al, 2008;Wouters et al, 2009;Szankasi et al, 2011;Ahmaed et al, 2012;Dufour et al, 2012;Greif et al, 2012;Kim et al, 2012). The 29% of the mutations constitute frames shift mutations generating a truncated protein, the remaining includes the missense mutations and aminoacid insertions.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Seventeen novel mutations were reported in the present study, remaining nine mutations were already reported in previous studies (Pabst et al, 2001;Leecharendkeat et al, 2008;Wouters et al, 2009;Szankasi et al, 2011;Ahmaed et al, 2012;Dufour et al, 2012;Greif et al, 2012;Kim et al, 2012). The 29% of the mutations constitute frames shift mutations generating a truncated protein, the remaining includes the missense mutations and aminoacid insertions.…”
Section: Discussionsupporting
confidence: 63%
“…We came across 3 types of polymorphisms, c.584_589dup ACCCGC, c.690G>T and c.573C>T. These three polymorphism has been reported in other studies (Frohling et al, 2004;Lin et al, 2005;Leecharendkeat et al, 2008;Fuchs et al, 2009;Kim et al, 2012). The c.584-589dup ACCCGC leading to p.P194_H195dup (proline-histidine duplication) was initially reported as mutation but later found as a germline polymorphism (Frohling et al, 2004;Lin et al, 2005;Resende et al, 2007;Wouters et al, 2007).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations